2021
DOI: 10.1186/s12887-020-02374-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cranial type characteristics in term infants: a multi-center study

Abstract: Background Positional head deformity (PHD) is defined as a change in the shape of an infant’s skull due to an external force. In certain cases, it can lead to cosmetic deformities or even neurological issues due to its impact on the developing nervous system. Therefore, we conducted this study to investigate the incidence and characteristics of PHD in term infants in China and preliminarily establish a localized diagnostic reference standard. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Head-shape problems are common among newborns and young children. Foreign studies have reported that the incidence of plagiocephaly in infants is 8.2-46.6% (1-3), while the incidence of head problems in 4,456 fullterm infants of 0-6 months in a Chinese study was about 56.5% (4). These findings suggest that the incidence of head problems in infants is common in the first few months after birth, and different races, regions, and cultures experience different cranial development.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Head-shape problems are common among newborns and young children. Foreign studies have reported that the incidence of plagiocephaly in infants is 8.2-46.6% (1-3), while the incidence of head problems in 4,456 fullterm infants of 0-6 months in a Chinese study was about 56.5% (4). These findings suggest that the incidence of head problems in infants is common in the first few months after birth, and different races, regions, and cultures experience different cranial development.…”
Section: Introductionmentioning
confidence: 83%
“…In this formula, α=0.05/2, β=0.1, δ is the allowable error, and σ is the standard deviation. Based on data acquired in our previous studies (4), in terms of cranial vault asymmetry index (CVAI), the mean difference between the spreading caliper and 3D measurements was approximately 0.57 mm, and the standard deviation was approximately 2.42 mm. According to literature reports (6), the allowable error is 1 mm, the confidence level is 1−x =0.95, the power of a test (1−β) was 0.9, and the number of samples required was 64.…”
Section: The Calculation Of Sample Sizementioning
confidence: 99%
“…Diagnostic criteria were based on the recommended diagnostic criteria of positional skull deformation in infants aged 0 to 6 months in Chongqing area [ 18 ]. Infants of different ages were grouped according to different types and degrees of PD (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is important for clinicians to note the specific landmarks and clinical techniques (e.g., manual or scanned) used by various researchers to obtain and report on cephalic width and length measurements. For example, anterior landmarks reported in various publications include the nasion, [22][23][24] glabella, 1,9,11,12,[19][20][21][25][26][27] or other (e.g., not specified, 2 cm above the nasion, middle of the nose, maximum length of the measurement plane, subnasal, sellion, nose tip, occipitofrontal diameter). 26,[28][29][30][31][32][33][34][35][36] Posterior landmarks may be the opisthocranion, 1,9,11,12,20,21,24,26,27 inion, 23 occipital protuberance, 19,22,25,30 or other (e.g., not specified, most projecting point at the back of the head, maximum length of measurement plane, occiput, greatest cranial length).…”
Section: Anatomical Landmarks and Alignments Used In CI Measurementsmentioning
confidence: 99%
“…For example, anterior landmarks reported in various publications include the nasion, [22][23][24] glabella, 1,9,11,12,[19][20][21][25][26][27] or other (e.g., not specified, 2 cm above the nasion, middle of the nose, maximum length of the measurement plane, subnasal, sellion, nose tip, occipitofrontal diameter). 26,[28][29][30][31][32][33][34][35][36] Posterior landmarks may be the opisthocranion, 1,9,11,12,20,21,24,26,27 inion, 23 occipital protuberance, 19,22,25,30 or other (e.g., not specified, most projecting point at the back of the head, maximum length of measurement plane, occiput, greatest cranial length). 19,25,28,29,[33][34][35][37][38][39] Lateral skull landmarks are the most varied and include the eurion, 12,24 bipari...…”
Section: Anatomical Landmarks and Alignments Used In CI Measurementsmentioning
confidence: 99%